The Rural Adult: A Portrait of Characteristics, Needs and Styles - Roger S. McCannon (Educational Considerations, 1986)
Early studies of rural adult learners suggested that most rural adults were interested only in recreational or avocational learning. A recent study which analyzed both regional and national demographic data suggests otherwise. This study provides us with a clearer picture of the learning needs and characteristics of rural adult learners.